2019
DOI: 10.3389/fmicb.2019.00804
|View full text |Cite
|
Sign up to set email alerts
|

Enterobacter cloacae, an Endophyte That Establishes a Nutrient-Transfer Symbiosis With Banana Plants and Protects Against the Black Sigatoka Pathogen

Abstract: Banana ( Musa spp.) is an important crop worldwide, but black Sigatoka disease caused by the fungus Pseudocercospora fijiensis threatens fruit production. In this work, we examined the potential of the endophytes of banana plants Enterobacter cloacae and Klebsiella pneumoniae , as antagonists of P. fijiensis and support plant growth in nutrient limited soils by N-transfer. The two bacterial isolat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 64 publications
1
40
0
1
Order By: Relevance
“… 2002 ; Macedo-Raygoza et al . 2019 ) and Enterobacter sp. J49, a biofertilizer for peanut and maize (Ludueña et al .…”
Section: Discussionmentioning
confidence: 99%
“… 2002 ; Macedo-Raygoza et al . 2019 ) and Enterobacter sp. J49, a biofertilizer for peanut and maize (Ludueña et al .…”
Section: Discussionmentioning
confidence: 99%
“…The Enterobacter strains are well-known nitrogen fixers, plant colonizers, and highly resistant to biotic and abiotic stresses ( English et al, 2010 ; Zhu et al, 2013 ; Sarkar et al, 2018 ; Macedo-Raygoza et al, 2019 ). All selected strains showed significant biocontrol activities against several pathogens used by dual culture method, and E. roggenkampii (ED5) showed highest antagonistic activity against F. moniliforme , F. cubense , B. cinerea , C. paradoxa , and S. scitamineum which indicates the potential application for management of diseases caused by various pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…PGPR can induce plant systemic tolerance (IST) by increasing the concentrations of dissolved phosphorus, ACC deaminase activity, volatile substances, iron carriers, and plant hormones ( Farag et al., 2013 ; Kumari S. et al., 2015 ). Some studies have shown the potential of E. cloacae to be a plant growth promoter and its characteristic of salt tolerant ( Bhise et al., 2016 ; Macedo-Raygoza et al., 2019 ). In the present study, ten strains were isolated from alkali-saline soil samples and screened to obtain E. cloacae HG-1 that had high salt tolerance.…”
Section: Discussionmentioning
confidence: 99%